A STRATEGIC FRAMEWORK FOR THE ADVANCEMENT OF DIGITAL CREATIVE INDUSTRY IN INDONESIA - Tan, Monica; Chandra, Michael; Jurmasari, Sriyanah; Harun, Tamara Destyani; Muchtar; Firman, Afrizal (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Indonesia's digital creative industry is a key driver of national economic growth, thanks to a young population that is comfortable with technology. But even though it has a lot of potential, the industry has ongoing structural problems that make it hard to stay competitive in the long run. These include a big gap between the skills that schools teach and what businesses need, unevendigital infrastructure, weak protection of intellectual property, and broken governance. People want free content and businesses that compete on price, which makes it even harder for businesses to innovate and stay in business. This study presents a strategic framework aimed at fortifying the industry, utilizing Porter’s Diamond Model as the analytical foundation. We use a quantitative explanatory approach backed by secondary data to look at factor conditions, demand conditions, related and supporting industries, firm strategy and competition, and the effects of government and chance. The results show that we need a development strategy that is based on four pillars: improving human capital, digital infrastructure, and ecosystem support; boosting innovation and business competitiveness; and making regulatory coordination more efficient. By following these steps, Indonesia can become a leader in theglobal digital economy by creating a more competitive, inclusive, and sustainable creative ecosystem.